Insights Into a Chlamydia pneumoniae-Specific Gene Cluster of Membrane Binding Proteins - Braun, Corinna; Hegemann, Johannes H.; Mölleken, Katja (Frontiers in Cellular and Infection Microbiology, 2020)
Chlamydia pneumoniae is an obligate intracellular pathogen that causes diseases of the upper and lower respiratory tract and is linked to a number of severe and chronic conditions. Here, we describe a large, C. pneumoniae-specific cluster of 13 genes (termed mbp1-13) that encode highly homologous chlamydial proteins sharing the capacity to bind to membranes. The gene cluster is localized on the chromosome between the highly diverse adhesin-encoding pmp genes pmp15 and pmp14. Comparison of human clinical isolates to the predicted ancestral koala isolate indicates that the cluster was acquired in the ancestor and was adapted / modified during evolution. SNPs and IN/DELs within the cluster are specific to isolates taken from different human tissues and show an ongoing adaptation. Most of the cluster proteins harbor one or two domains of unknown function (DUF575 and DUF562). During ectopic expression in human cells these DUF domains are crucial for the association of cluster proteins to the endo-membrane system. Especially DUF575 which harbors a predicted transmembrane domain is important for binding to the membrane, while presence of the DUF562 seems to be of regulatory function. For Mbp1, founding member of the cluster that exhibits a very limited sequence identity to the human Rab36 protein, we found a specific binding to vesicles carrying the early endosomal marker PtdIns(3)P and the endosomal Rab GTPases Rab11 and Rab14. This binding is dependent on a predicted transmembrane domain with an -helical / β-strand secondary structure, as the mutant version Mbp1mut, which lacks the β-strand secondary structure, shows a reduced association to PtdIns(3)P-positive membranes carrying Rab11 and Rab14. Furthermore, we could not only show that Mbp1 associates with Rab36, but found this specific Rab protein to be recruited to the early C. pneumoniae inclusion. Detection of endogenous Mbp1 and Mbp4 reveal a colocalization to the chlamydial outer membrane protein Momp on EBs. The same colocalization pattern with Momp was observed when we ectopically expressed Mbp4 in C. trachomatis. Thus, we identified a C. pneumoniae-specific cluster of 13 membrane binding proteins (Mbps) localizing to the bacterial outer membrane system.